Analysis of Production Cost and Revenue Budget to Support the Effectiveness of Production Cost Control in Making Dimsum at Adidimsum Medan - Rangkuty, Fathia Mawaddah; Atika, Atika; Nasution, Yenni Samri Juliati (Amkop Management Accounting Review (AMAR), 2025)
Micro, small, and medium enterprises (MSMEs) are strategic sectors in encouraging national economic growth, one of which is through home industries engaged in processed food. This study aims to analyze the structure of the cost budget and production income and evaluate the effectiveness of cost control in the Home Industry of Adidimsum Medan Karya. The research method used is qualitative descriptive with a case study approach, using primary data obtained through direct interviews and documentation from business owners. The results of the study show that the total monthly production cost is IDR 61,870,000, while the income obtained reaches IDR 110,000,000, so that a profit margin of IDR 48,130,000 is obtained. Although this business has considerable profit potential, budget management has not been carried out in a structured manner, still using manual methods without digital or systematic recording. This risks causing cost leakage that can reduce production efficiency. Therefore, more effective cost control strategies are needed, such as the separation between fixed and variable costs, as well as the use of a simple integrated financial recording system. This research is expected to provide a real and practical picture for home food business actors in managing costs and income efficiently in order to maintain the continuity and competitiveness of their businesses in the midst of growing market competition.